Surviving the breakup how children and parents cope with divorce - Wallerstein, Judith S.; Kelly, Joan B. (Grant McIntyre, 1980)
Advice for the professionals who are in contact with divorcing families and to the individuals seeking divorce and their concern for the children involved.